Method for manufacturing electrolytic copper foil with high elongation characteristic after high-temperature heat treatment

By adding specific additives to the electrolytic copper foil manufacturing process and performing high-temperature heat treatment, the problem of low elongation caused by volume changes of lithium-ion batteries is solved, and electrolytic copper foil with high elongation is produced, satisfying the lithium-ion battery and cylindrical battery The market demand for high elongation improves the stability and life of the battery.

CN119307986APending Publication Date: 2025-01-14SHAANXI FUTURE ADVANCED MATERIALS TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411464655.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The low elongation of material caused by volume changes in lithium-ion batteries during charging/discharging leads to battery stability and life problems. Especially in the emerging cylindrical battery market, existing electrolytic copper foils cannot meet the demand for high elongation.

Method used

By adding specific additives, such as sulfur-containing compounds, nitrogen-containing heterocyclic compounds, nonionic water-soluble polymers and collagen, electrolytic copper foils with high elongation after high temperature heat treatment, the specific steps include The electrolyte is added with disodium salt of thiophosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester, 2-mercaptobenzothiazole, β-naphthol polyethylene glycol ether and fish gel, and After 190°C heat treatment for 1 hour, electrolytic copper foil was formed.

Benefits of technology

The electrolytic copper foil produced has an elongation of 15% to 19% at room temperature, which can effectively cope with the volume changes of lithium-ion batteries during charging/discharging, meet the physical performance requirements of the cylindrical battery industry for high elongation, and improve the battery. stability and lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092932510000101
    Figure BDA0005092932510000101
  • Figure BDA0005092932510000102
    Figure BDA0005092932510000102
  • Figure BDA0005092932510000111
    Figure BDA0005092932510000111
Patent Text Reader

Abstract

The invention provides a manufacturing method of an electrolytic copper foil with a high elongation characteristic after high-temperature heat treatment, and belongs to the technical field of electrolytic copper foils. Comprising the following steps: (1) preparing an electrolyte from sulfuric acid, copper and high-purity water in an electrolytic bath; (2) an electrolytic copper foil additive is added into the electrolyte; the electrolytic copper foil additive is prepared from the following components in mass concentration: a sulfur-containing compound additive A with the content of 10 mg / L to 21 mg / L, a nitrogen-containing heterocyclic compound additive B with the content of 8 mg / L to 18 mg / L, a nonionic water-soluble polymer additive C with the content of 5 mg / L to 12 mg / L and a collagen additive D with the content of 2 mg / L to 8 mg / L, and (3) the anode plate and the rotating cathode roller which are separated from each other in the electrolyte in the electrolytic bath are powered on, and electrolytic copper foil is formed on the surface of the cathode roller. The electrolytic copper foil prepared by using the additive has the characteristic of high elongation after being subjected to heat treatment at 190 DEG C for 1 hour.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic copper foil, and in particular relates to a method for manufacturing an electrolytic copper foil having high elongation characteristics after high-temperature heat treatment. Background Art

[0002] Lithium-ion batteries use electrolytic copper foil as the negative electrode current collector material. As electric cars, which are known as environmentally friendly cars, gain popularity, the demand for lithium-ion batteries continues to increase. At the same time, high-performance copper foil is required to achieve high efficiency, high capacity, and high quality of batteries.

[0003] Generally speaking, in order to improve the performance of batteries, the thickness, tensile strength, elongation, roughness and other physical properties of electrolytic copper foil must be excellent, but this is of course not easy, and many electrolytic copper foil manufacturers are constantly researching and developing. The elongation of the above-mentioned physical properties of electrolytic copper foil plays an important role in the stability and life of the battery. The reason is that lithium-ion batteries have a reversible change of swelling (Swelling) between charge / discharge. As the charge / discharge continues, this volume change occurs repeatedly. If the elongation of the material is low, it cannot withstand the volume change, cracking or reducing the battery life. In order to prevent this from happening, it is necessary to manufacture electrolytic copper foil with better elongation.

[0004] In addition, cylindrical batteries such as 4680, which have recently become a hot topic in the battery industry, require a higher elongation because the positive electrode, separator, negative electrode and other materials are rolled up in sequence to form a battery pack.

[0005] Therefore, in order to cope with the volume changes of lithium-ion batteries and the cylindrical battery market brought about by the continuous development, copper foil with high elongation characteristics is needed. Summary of the invention

[0006] The technical problem solved by the present invention is to provide a method for manufacturing an electrolytic copper foil having high elongation characteristics after high-temperature heat treatment. The purpose of the present invention is to improve the additives of the electrolytic copper foil so that the prepared electrolytic copper foil has high elongation characteristics after heat treatment at 190°C for 1 hour.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for manufacturing an electrolytic copper foil having high elongation characteristics after high temperature heat treatment comprises the following steps:

[0009] Step 1): preparing an electrolyte in an electrolytic cell using sulfuric acid, copper and high-purity water;

[0010] Step 2): adding an electrolytic copper foil additive to the electrolyte;

[0011] Wherein, the electrolytic copper foil additive is composed of the following components in mass concentration:

[0012] Sulfur compound additive A, content of 10mg / L to 21mg / L,

[0013] Nitrogen-containing heterocyclic compound additive B, content of 8mg / L to 18mg / L,

[0014] Non-ionic water-soluble polymer additive C, content of 5 mg / L to 12 mg / L,

[0015] Collagen additive D, content of 2 mg / L to 8 mg / L;

[0016] Step 3): Electrolytic copper foil is formed on the surface of the cathode roller by electrifying the anode plates and the rotating cathode roller spaced apart from each other in the electrolyte in the electrolytic cell.

[0017] To further limit the above scheme, the sulfur-containing compound additive A is one of 3-N,N-dimethylthiocarbamoyl-thiopropanesulfonic acid sodium salt, 3-amino-aminomethylthio-1-propanesulfonic acid sodium salt, 3-dimercapto-1-propanesulfonic acid, 3-benzothiazoline-2-mercaptopropanesulfonic acid, and disodium phosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester.

[0018] To further limit the above scheme, the nitrogen-containing heterocyclic compound additive B is one of 2-mercapto-5-benzimidazole sulfonic acid sodium salt, 2-mercaptobenzothiazole salt, and 3-5-mercapto-1-tetrazolylbenzenesulfonic acid sodium salt.

[0019] To further limit the above scheme, the nonionic water-soluble polymer additive C is a nonionic water-soluble polymer, which is one of polyethylene glycol, hydroxyethyl cellulose, polyethylene glycol, oleic acid polyethylene glycol ether, polyethylene glycol dimethyl ether, polyvinyl alcohol, polyglycerol, and β-naphthol polyethylene glycol ether.

[0020] To further limit the above scheme, the collagen additive D is fish glue.

[0021] To further define the above scheme, the basic composition of the electrolyte contains 70g / l to 130g / l sulfuric acid (H2SO4), 60g / l to 130g / l copper ions (Cu2+), and 15mg / l to 25mg / l chloride ions (Cl-).

[0022] Further limitation of the above scheme, the temperature of the electrolyte is 40°C to 60°C, the current density is 30A / dm 2 Up to 55A / dm 2 , the electrolyte was treated with charcoal-based activated carbon.

[0023] Further limitation of the above scheme, the electrolytic copper foil manufactured by the above method has a room temperature tensile strength of 30kgf / mm after heat treatment at 190°C for 1 hour. 2 Up to 35kgf / mm 2 After heat treatment at 190°C for 1 hour, the room temperature elongation is 15% to 19%, the surface roughness Rz of the M surface is less than 2.2μm, and the glossiness (Gs(60°) of the M surface is greater than 90 and less than 150; the thickness of the electrolytic copper foil manufactured by the above method is 4.5μm to 8μm.

[0024] The advantages of the present invention compared with the prior art are:

[0025] 1. In the process of manufacturing the electrolytic copper foil of this scheme, the additives added to the electrolyte are sulfur compound additive A: disodium salt of phosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester, nitrogen heterocyclic compound additive B: 2-mercaptobenzothiazole, non-ionic water-soluble polymer additive C: β-naphthol polyethylene glycol ether, and collagen additive D: fish glue. By using the above additives to prepare electrolytic copper foil, after heat treatment at 190°C for 1 hour, electrolytic copper foil with high elongation characteristics can be manufactured, and the room temperature elongation reaches 15% to 19%, which has a high elongation;

[0026] 2. In this way, the present invention can cope with the volume change that occurs during charging / discharging for lithium-ion batteries using the electrolytic copper foil manufactured according to the present invention, and can manufacture batteries by sequentially winding battery components such as the positive electrode, separator and negative electrode, thereby meeting the physical properties required by the cylindrical battery industry that requires high elongation. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] A method for manufacturing an electrolytic copper foil having high elongation characteristics after high temperature heat treatment comprises the following steps:

[0029] Step 1): preparing an electrolyte in an electrolytic cell using sulfuric acid, copper and high-purity water;

[0030] Step 2): adding an electrolytic copper foil additive to the electrolyte;

[0031] Wherein, the electrolytic copper foil additive is composed of the following components in mass concentration:

[0032] Sulfur compound additive A, content of 10mg / L to 21mg / L,

[0033] Nitrogen-containing heterocyclic compound additive B, content of 8mg / L to 18mg / L,

[0034] Non-ionic water-soluble polymer additive C, content of 5 mg / L to 12 mg / L,

[0035] Collagen additive D, content of 2 mg / L to 8 mg / L;

[0036] Step 3): Electrolytic copper foil is formed on the surface of the cathode roller by electrifying the anode plates and the rotating cathode roller spaced apart from each other in the electrolyte in the electrolytic cell.

[0037] The foil machine used to produce electrolytic copper foil has a structure in which a rotating cathode roller and a circular anode plate are installed separately, wherein the anode plate is in the electrolyte. In addition, the cathode roller and the anode plate are divided into negative and positive poles respectively to apply current suitable for each polarity.

[0038] In a preferred embodiment, the sulfur-containing compound additive A is one of 3-N,N-dimethylthiocarbamoyl-thiopropanesulfonic acid sodium salt, 3-amino-aminomethylthio-1-propanesulfonic acid sodium salt, 3-dimercapto-1-propanesulfonic acid, 3-benzothiazoline-2-mercaptopropanesulfonic acid, and disodium phosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester.

[0039] In a preferred embodiment, the nitrogen-containing heterocyclic compound additive B is one of 2-mercapto-5-benzimidazole sulfonic acid sodium salt, 2-mercaptobenzothiazole salt, and 3-5-mercapto-1-tetrazolylbenzenesulfonic acid sodium salt.

[0040] In a preferred embodiment, the nonionic water-soluble polymer additive C is one of polyethylene glycol, hydroxyethyl cellulose, polyethylene glycol, oleic acid polyethylene glycol ether, polyethylene glycol dimethyl ether, polyvinyl alcohol, polyglycerol, and β-naphthol polyethylene glycol ether.

[0041] In a preferred embodiment, the collagen additive D is fish glue.

[0042] The above-mentioned additives in the present invention are:

[0043] Additive A is a sulfur-containing compound used to improve the surface brightness of the electrolytic copper foil. When the content of the above-mentioned additive A is less than 10 mg / L, the surface roughness of the electrolytic copper foil will increase and the brightness will decrease. When the content of the above-mentioned additive A exceeds 21 mg / L, the surface roughness will also increase and the brightness will decrease.

[0044] Among the above additives, additive B is a nitrogen-containing heterocyclic compound used to improve the tensile strength of the electrolytic copper foil. When the content of the above additive B is less than 8 mg / L, the tensile strength may decrease, and when the content of the above additive B exceeds 18 mg / L, the surface roughness increases, it is difficult to have a low roughness, and the tensile strength and elongation are also reduced.

[0045] Among the above additives, additive C is a non-ionic water-soluble polymer, which can reduce the surface roughness of the electrolytic copper foil when used together with additive D. When the content of the above additive C is less than 5 mg / L, the surface roughness will increase and the surface brightness will decrease. When the content of the above additive C exceeds 12 mg / L, the surface roughness will increase, it is difficult to have a low roughness, and the tensile strength will also decrease.

[0046] Among the above additives, additive D is a collagen, which effectively improves the initial elongation of the electrolytic copper foil when used together with additive C. If the content of the above additive D is less than 2 mg / L, it is difficult to achieve an increase in elongation, and if the content of the above additive D exceeds 8 mg / L, the elongation will decrease instead.

[0047] In the above-mentioned preparation method, the basic composition of the electrolyte contains 70g / l to 130g / l sulfuric acid (H2SO4), 60g / l to 130g / l copper ions (Cu2+), and 15mg / l to 25mg / l chloride ions (Cl-).

[0048] The temperature of the electrolyte is 40°C to 60°C, and the current density is 30A / dm 2 Up to 55A / dm 2 , the electrolyte was treated with charcoal-based activated carbon.

[0049] The electrolytic copper foil produced by the above method has a room temperature tensile strength of more than 55kgf / mm before heat treatment. 2 , after heat treatment at 190℃ for 1 hour, the room temperature tensile strength is 30kgf / mm 2 Up to 35kgf / mm 2 . In addition, the room temperature elongation of the electrolytic copper foil before heat treatment is 7% to 10%, and the volume change during battery charging / discharging may cause cracks or reduce battery life; after heat treatment at 190°C for 1 hour, the room temperature elongation is 15% to 19%, which has a high elongation. The surface roughness Rz of the M surface of the electrolytic copper foil is less than 2.2μm, and the glossiness (Gs (60°) of the M surface is greater than 90 and less than 150. The thickness of the electrolytic copper foil manufactured by the above method is 4.5μm to 8μm.

[0050] The properties of the electrolytic copper foil prepared by the present invention are specifically described below through examples and comparative examples.

[0051] Example 1

[0052] The foil production machine is composed of a rotating cathode roller and an anode plate in the electrolyte in the electrolytic cell, and the cathode roller is energized to form electrolytic copper foil.

[0053] In addition, the electrolytic conditions of the electrolytic copper foil manufactured in this embodiment 1, i.e., the basic composition of the electrolyte is 105.5 g / l of sulfuric acid (H2SO4), 85.5 g / l of copper ions (Cu2+), and 17 mg / l of chloride ions (Cl-). Then, the following additives are added to the above electrolyte:

[0054] Sulfophosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester disodium salt 10.3㎎ / L 2-Mercaptobenzothiazole 8.4㎎ / L

[0055] β-Naphthol Polyglycol Ether 5.5㎎ / L

[0056] Fish glue 2.2㎎ / L

[0057] At this time, the temperature of the electrolyte is 53±1℃ and the current density is 35A / dm 2 .

[0058] In addition, charcoal-based activated carbon treatment was performed for high temperature elongation.

[0059] The electrolytic copper foil was formed into a thickness of 6 μm, and the produced electrolytic copper foil was subjected to heat treatment at 190° C. for 1 hour.

[0060] Example 2

[0061] An electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows.

[0062] Sulfophosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester disodium salt 12.3㎎ / L 2-Mercaptobenzothiazole 10.1㎎ / L

[0063] β-Naphthol Polyglycol Ether 6.7㎎ / L

[0064] Fish glue 3.4㎎ / L

[0065] Example 3

[0066] An electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows.

[0067] Sulfophosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester disodium salt 14.4㎎ / L 2-Mercaptobenzothiazole 11.9㎎ / L

[0068] β-Naphthol Polyglycol Ether 8.0㎎ / L

[0069] Fish glue 4.5㎎ / L

[0070] Example 4

[0071] An electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows.

[0072] Phosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester disodium salt

[0073] 2-Mercaptobenzothiazole 13.8㎎ / L

[0074] β-Naphthol Polyglycol Ether 9.1㎎ / L

[0075] Fish glue 5.7㎎ / L

[0076] Example 5

[0077] The electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows. Disodium phosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester 18.8 mg / L

[0078] 2-Mercaptobenzothiazole 15.7㎎ / L

[0079] β-Naphthol Polyglycol Ether 10.3㎎ / L

[0080] Fish glue 6.8㎎ / L

[0081] Example 6

[0082] The electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows: Sulfophosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester disodium salt 20.8 mg / L

[0083] 2-Mercaptobenzothiazole 17.3㎎ / L

[0084] β-Naphthol Polyglycol Ether 11.4㎎ / L

[0085] Fish glue 8.0㎎ / L

[0086] Comparative Example 1

[0087] The electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows: Sulfophosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester disodium salt 7.8 mg / L

[0088] 2-Mercaptobenzothiazole 5.7㎎ / L

[0089] β-Naphthol Polyethylene Glycol Ether 3.2㎎ / L

[0090] Fish glue 0.5㎎ / L

[0091] Comparative Example 2

[0092] The electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows: Sulfophosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester disodium salt 10.1 mg / L

[0093] 2-Mercaptobenzothiazole 8.2㎎ / L

[0094] β-Naphthol Polyglycol Ether 5.4㎎ / L

[0095] Comparative Example 3

[0096] The electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows: Sulfophosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester disodium salt 13.5 mg / L

[0097] 2-Mercaptobenzothiazole 11.0㎎ / L

[0098] β-Naphthol Polyethylene Glycol Ether 7.4㎎ / L

[0099] Fish glue 1.2㎎ / L

[0100] Comparative Example 4

[0101] The electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows. Sulfophosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester disodium salt 17.8 mg / L

[0102] 2-Mercaptobenzothiazole 14.7㎎ / L

[0103] β-Naphthol Polyglycol Ether 3.5㎎ / L

[0104] Fish glue 6.2㎎ / L

[0105] Comparative Example 5

[0106] The electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows. Disodium phosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester 20.9 mg / L

[0107] 2-Mercaptobenzothiazole 17.8㎎ / L

[0108] Fish glue 7.9㎎ / L

[0109] Comparative Example 6

[0110] The electrolytic copper foil was prepared in the same manner as in Example 1 except that the contents of the additives were as follows. Disodium phosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester 24.6 mg / L

[0111] 2-Mercaptobenzothiazole 21.0㎎ / L

[0112] β-Naphthol Polyglycol Ether 14.0㎎ / L

[0113] Fish maw 10.0㎎ / L.

[0114] Regarding the additives and contents of the electrolytic copper foil manufactured according to the present invention, Examples 1 to 6 and Comparative Examples 1 to 6 are shown in Table 1; the thickness, surface roughness Rz of the M surface, brightness of the M surface, elongation at room temperature before heat treatment, elongation at room temperature after heat treatment at 190°C for 1 hour, tensile strength at room temperature before heat treatment, and tensile strength at room temperature after heat treatment at 190°C for 1 hour are measured and shown in Table 2 below.

[0115] Table 1

[0116]

[0117] Table 2

[0118]

[0119]

[0120] Results: As shown in Table 1 and Table 2, the room temperature elongation of the electrolytic copper foils of Examples 1 to 6 after heat treatment at 190°C for 1 hour is greater than 15%. When only one additive is added from Additive C and Additive D, and when the same additive is added but the additive content is lower than the standard value, it can be confirmed that the room temperature elongation of the electrolytic copper foils of Comparative Examples 2 to 5 after heat treatment at 190°C for 1 hour is less than 11%. When all additives are lower than the standard value or exceed the standard, the room temperature elongation of the electrolytic copper foils of Comparative Examples 1 to 6 after heat treatment at 190°C for 1 hour is lower than 11%.

[0121] When the above-mentioned high elongation electrolytic copper foil is used, the volume change of lithium-ion batteries during charging and discharging can be coped with. In particular, it can cope with the high elongation electrolytic copper foil market required when the battery constituent materials such as anodes, cathodes, and separators are sequentially composed of cylindrical battery cells. When using electrolytic copper foil with low elongation such as the comparative example, it may not be able to withstand the volume change of lithium-ion batteries during charging / discharging and crack or reduce the battery life, and may not meet the requirements of the continuously developing cylindrical battery market.

[0122] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0123] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for producing an electrolytic copper foil having high elongation characteristics after high temperature heat treatment, characterized in that: The following steps are involved: Step 1): preparing an electrolyte in an electrolytic cell using sulfuric acid, copper and high-purity water; Step 2): adding an electrolytic copper foil additive to the electrolyte; Wherein, the electrolytic copper foil additive is composed of the following components in mass concentration: Sulfur compound additive A, content of 10mg / L to 21mg / L, Nitrogen-containing heterocyclic compound additive B, content of 8mg / L to 18mg / L, Non-ionic water-soluble polymer additive C, content of 5 mg / L to 12 mg / L, Collagen additive D, content of 2 mg / L to 8 mg / L; Step 3): Electrolytic copper foil is formed on the surface of the cathode roller by electrifying the anode plates and the rotating cathode roller spaced apart from each other in the electrolyte in the electrolytic cell.

2. The method for producing an electrolytic copper foil having high elongation characteristics after high temperature heat treatment according to claim 1, characterized in that: The sulfur-containing compound additive A is one of 3-N,N-dimethylthiocarbamoyl-thiopropanesulfonic acid sodium salt, 3-amino-aminomethylthio-1-propanesulfonic acid sodium salt, 3-dimercapto-1-propanesulfonic acid, 3-benzothiazoline-2-mercaptopropanesulfonic acid, and disodium phosphatidic acid-o-ethyl-bis-(o-sulfopropyl) ester.

3. The method for producing an electrolytic copper foil having high elongation characteristics after high temperature heat treatment according to claim 1, characterized in that: The nitrogen-containing heterocyclic compound additive B is one of 2-mercapto-5-benzimidazole sulfonic acid sodium salt, 2-mercaptobenzothiazole salt, and 3-5-mercapto-1-tetrazolylbenzenesulfonic acid sodium salt.

4. The method for producing an electrolytic copper foil having high elongation characteristics after high temperature heat treatment according to claim 1, characterized in that: The nonionic water-soluble polymer additive C is one of polyethylene glycol, hydroxyethyl cellulose, polyethylene glycol, oleic acid polyethylene glycol ether, polyethylene glycol dimethyl ether, polyvinyl alcohol, polyglycerol, and β-naphthol polyethylene glycol ether.

5. The method for producing an electrolytic copper foil having high elongation characteristics after high temperature heat treatment according to claim 1, characterized in that: The collagen additive D is fish glue.

6. The method for producing an electrolytic copper foil having high elongation characteristics after high temperature heat treatment according to claim 1, characterized in that: The basic composition of the electrolyte contains 70g / l to 130g / l sulfuric acid H2SO4, 60g / l to 130g / l copper ions Cu2+, and 15mg / l to 25mg / l chloride ions Cl-.

7. The method for producing an electrolytic copper foil having high elongation characteristics after high temperature heat treatment according to claim 1, characterized in that: The temperature of the electrolyte is 40°C to 60°C, and the current density is 30A / dm 2 Up to 55A / dm 2 , the electrolyte was treated with charcoal-based activated carbon.

8. The method for producing an electrolytic copper foil having high elongation characteristics after high temperature heat treatment according to claim 1, characterized in that: The electrolytic copper foil produced by the above method has a room temperature tensile strength of 30 kgf / mm after heat treatment at 190°C for 1 hour. 2 Up to 35kgf / mm 2 After heat treatment at 190°C for 1 hour, the room temperature elongation is 15% to 19%, the surface roughness Rz of the M surface is less than 2.2μm, and the glossiness (Gs(60°) of the M surface is greater than 90 and less than 150; the thickness of the electrolytic copper foil manufactured by the above method is 4.5μm to 8μm.

Citation Information

Cited By

  • Electrolytic copper foil suitable for new generation AI and communication industry and manufacturing method thereof

    CN119932655A